국립순천대학교 교양교육과정 개편에 따른<독서와 표현> 영역 개설안 - 김철신(Kim, Chul-shin); 박상태(Park, Sang-tae) (교양교육연구, 2015)
이 논문의 목적은 2015학년도 국립순천대학교 교양교육과정의 개편과 이에 따른 신설 핵심교양 영역인 <독서와 표현> 및 이 영역의 세부 교과목들인 <독서와 생각하기>, <독서와 말하기>, <독서와 글쓰기>의 교육 목적, 개요와 특징, 공통 수업 내용, 그리고 주차별 수업 계획서 등을 소개하는 것이다. 2015학년도 국립순천대학교 교양교육과정 개편의 핵심은 정보화 및 세계화 시대를 맞아 정보와 자료를 논리적으로 분석하고, 이를 비판적으로 평가하며, 이러한 정보와 자료를 재구성하여 새로운 지식을 창의적으로 생산하는 교양교육을 제공하는 데 있다. 이를 위해 신설된 <독서와 표현> 영역과 이 영역의 세부 교과목들은 비판적 사고 운동과 이에 근거한 말하기 및 글쓰기 의사소통교육을 융합한 자기 주도적 기초 학습 능력을 향상시키기 위한 교과목들로서, 그동안 학과 교양필수 영역 지정으로 인해 제약을 받았던 교양 교과목에 대한 학생 선택권을 강화하고 교양교육과정의 고유성과 체계성을 회복하는 국립순천대학교의 새로운 교양교육과정이다. 아직 <독서와 표현> 영역과 세부 교과목들의 운영과 관련하여 많은 문제점과 시행착오가 예상되지만, 대학 구성원들의 관심과 노력에 힘입어 앞으로 이 영역과 세부 교과목들이 새로운 시대를 대비하는 국립순천대학교의 대표적 교양교육으로 자리 잡을 수 있기를 희망한다. The purpose of this thesis is to introduce reorganization of Suncheon National University’s liberal education curriculum for the 2015 academic year together with <Reading and Expression>, key area of newly-established liberal education curriculum according to the reorganization, and educational objectives, outline and features, common contents of class and weekly syllabus of <Reading and Thinking>, <Reading and Speaking>, <Reading and Writing> which are the detailed subjects of the area. The core of Suncheon National University’s reorganization of liberal education curriculum for the 2015 academic year is to provide liberal education capable of producing new knowledge creatively by analyzing information and data in a logical way, evaluating them critically and reconstituting such information and data facing the era of informatization and globalization. Newly-established for the foregoing, <Reading and Expression> area and detailed subjects of the area are the ones to improve critical thinking movement and self-initiated basic learning ability that converged speaking, writing and communication education, which are the new liberal education curriculum for Suncheon National University to strengthen students’ right of choice with respect to the liberal arts subjects that have had restrictions by being designated as a compulsory liberal education area of department, and to recover uniqueness and system of liberal education curriculum. Although many trials and errors as well as problems are expected related to the operation of <Reading and Expression> area and its detailed subjects yet, we hope that the area and its detailed subjects can settle down as the representative liberal education of Suncheon National University indebted to university members’ interest and efforts in making provision for a new era. KCI Citation Count: 4